2g+4(-8+3g)=1-g

Simple and best practice solution for 2g+4(-8+3g)=1-g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2g+4(-8+3g)=1-g equation:


Simplifying
2g + 4(-8 + 3g) = 1 + -1g
2g + (-8 * 4 + 3g * 4) = 1 + -1g
2g + (-32 + 12g) = 1 + -1g

Reorder the terms:
-32 + 2g + 12g = 1 + -1g

Combine like terms: 2g + 12g = 14g
-32 + 14g = 1 + -1g

Solving
-32 + 14g = 1 + -1g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add 'g' to each side of the equation.
-32 + 14g + g = 1 + -1g + g

Combine like terms: 14g + g = 15g
-32 + 15g = 1 + -1g + g

Combine like terms: -1g + g = 0
-32 + 15g = 1 + 0
-32 + 15g = 1

Add '32' to each side of the equation.
-32 + 32 + 15g = 1 + 32

Combine like terms: -32 + 32 = 0
0 + 15g = 1 + 32
15g = 1 + 32

Combine like terms: 1 + 32 = 33
15g = 33

Divide each side by '15'.
g = 2.2

Simplifying
g = 2.2

See similar equations:

| 3y-2(y-1)/6=-2 | | -1/5r=24/5 | | 12(x+8)=4(24+3n) | | xb=-7 | | -9=11m-3.4 | | 88x-55=y | | 0.8x-10=2.3x-25 | | 4(x-30)=5-3x | | a-b=x | | 12x/35-x/7=1 | | 55=4x+y | | 3x+21=46-2x | | 2t^2=30t | | 0.005(x+3)=0.006x+0.013 | | 378g*6=47g | | -2x-5x=9x-12 | | 26x+8=5(5x+6) | | 4/9//-5/6 | | 2b/3a÷4b/9a^4b^5 | | 2a-3a=a | | 16x^2=-121 | | X^2/3-9/49=0 | | 7p-3(p+8)=-4(6-p) | | 9y-6-7y=8 | | 6x^3-44x^2+14x=0 | | x/15=3/2 | | x/1/5=3/2 | | 10(4-8x)+1=X-7 | | y/2=x-9 | | 12x-3x=5x-4+8x | | 9x-90=3x-18 | | x*1/2=2/3 |

Equations solver categories